Are nanomaterials leading to more efficient agriculture? Outputs from 2009 to 2022 research metadata analysis - Santos, E.; Montanha, G. S.; Gomes, M. H. F.; Duran, N. M.; Correa, C. G.; Romeu, S. L. Z.; Pereira, A. E. S. [UNESP]; Oliveira, J. L. [UNESP]; Almeida, E.; Perez-de-Luque, A.; Ghoshal, S.; Santaella, C.; et al. (Royal Soc Chemistry, 2022)
Agriculture is responsible for supplying food, feed, fibres, and an increasing fraction of fuel and raw chemicals for industry. Fulfilling such demands sustainably is one of the major challenges of our time. In this metadata analysis, we offer a quantitative overview of how scientists have been addressing the effects of nanomaterials on plants between 2009 and 2022. The analysis showed that cultivated crops (ca. 55%) and plant nutrients (54%) are mostly employed in the studies, pointing to the relevance of these aspects to agriculture. Nevertheless, it also revealed that the concentration of elements as nanomaterials is generally more than 2-fold higher than the elemental concentration applied as traditionally formulated fertilisers or those naturally found in soil. Furthermore, the median time span of most studies, i.e., 49 days for plants cultivated in soil, is still quite short compared to annual crop life cycles (90-120 days), and little attention (19% of treatments) has been devoted to soil microorganisms. Also, only a small fraction of experiments (6%) has been carried out under field conditions. Therefore, the data did not allow establishing correlations between effects and experimental parameters, such as concentration range, soil pH, or time of exposure. These observations point to the intricate relationship between our ability to infer conclusions and the experimental design employed. Finally, this comprehensive and up-to-date overview of the effects of nanomaterials on plant systems raises the question of whether nanomaterials will lead to incremental yield gains by replacing current inputs with nanotechnology-based ones, such as the controlled release of fertilizers and pesticides, or will disrupt agriculture by attacking problems so far not practically addressed, such as hacking plant stress and defence mechanisms or modulating metabolism and photosystems.